Consolidating the budget under difficult conditions: Ten guidelines viewed against Europe's beginning consolidation programme - Karl Aiginger; Margit Schratzenstaller (Intereconomics, 2011)
There is evidence that a budget consolidation strategy can work with only a small and shortlived negative impact on growth. However, many countries are currently trying to consolidate at the same time as firms and consumers are deleveraging. We develop ten guidelines for consolidation during such a difficult economic period and cross-check whether the upcoming consolidation programmes being implemented in the EU countries comply with our guidelines. We propose following a 'high road' on cutting deficits, which includes an active growthenhancing component during the consolidation period. The active component should be financed by deeper cuts in subsidies, by eliminating obsolete government expenditure as well as by increasing the efficiency of the public sector. Taxes should not be raised permanently - a temporary contribution to consolidation will be needed, but tax structures in general should be made more growth and employment friendly.
Keywords: 330